(3JjSjQ GdeWGdH dcd WGdHs - (3CHh YHO Gddg TeS GdOjf eMeO Hf eMeO Hf jYbhH Gdchej GdJhfSjs
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf jYbhH Gdchei NjQ eG UOQJ Hg GdUMa GdEdgjGJ hETJedJ Ydjg ahGJM GdRHQ s
(3BNQgG (B:s
(3hEfeG gi JMdjGJ CSeGFjI ai eXGgQ eKGdjI EMJLJ HgG Yf CHUGQ GdWGdHjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd hCTcGds
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eOQSI GdMLjGJ (B_ (3GdehUd (B(66) s
Keywords: (3GdeLGejYs